Pola Pendidikan Madrasah Berasrama Dalam Pembentukan Karakter Siswa - Muis, Abd.; Abd. Hayyi Akrom (Ta'dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2025)
This study's goal is to outline how MTsN 1 East Lombok's boarding madrasah education shapes students' personalities. Researchers employed a qualitative field research approach, gathering data through documentation, document analysis, interviews, and observation. The study's findings show that the boarding school model can integrate experiential, institutional, and natural education—all of which have a major impact on how MTsN 1 East Lombok students develop as individuals, especially when it comes to social care, independence, discipline, and responsibility. The educational approach of boarding schools can also foster and develop students' interests and abilities in the areas of spirituality and religion.